Metagenomic Next-Generation Sequencing to Investigate Infectious Endophthalmitis of Brucella: A Case Report - Xi, Huiyu; Zhang, Lishuai; Xu, Bo; Liu, Haiyang; Li, Suyan (Frontiers in Medicine, 2022)
Introduction Brucellosis is a systemic disease that exists prevalently in clinical manifestations. The symptoms present in organs such as the eyes (in ocular brucellosis) can lead to misdiagnosis or even failure to diagnose. Metagenomic Next-Generation Sequencing (mNGS), a high-throughput sequencing approach, could be applied for the detection of microorganisms. Case Presentation A 57-year-old female with acute right-eye vision loss, treated with clindamycin and dexamethasone sodium phosphate for 1.5 months, was difficult to diagnose using regular methods. mNGS was utilized for the aqueous fluid from the patient, and Brucella melitensis was identified. The inflammation was treated with 3 months of antibiotherapy. However, even with specific medicine and surgery, the vision remained poor because severe ocular conditions last for a long time. Conclusion It suggests that brucella should still be a probable pathogen in endophthalmitis despite its low incidence in non-epidemic areas. Moreover, mNGS can achieve early diagnosis and timely treatment for difficult-to-diagnose ocular infections.